REGULATORY AND LEGAL REGULATION OF INCLUSIVE EDUCATION - Zairov Asadbek Sayfullo o‘g‘li (Bright Mind Publishing, 2025)
This study explores the methodological aspects of developing students' learning motivation through the philosophical and psychological analysis of literary works. It presents various ways to enhance motivation and provides recommendations on the theory and methods of forming learning motivation in literature lessons.
Keywords: Philosophical and psychological analysis, motivation, need, learning, education.